Решите уравнение 3(х-1)+х=2х , 5-х=4(х-3) , 5(х+4)+х=6 , 7-(2х+3)=9 , 3(х-7)-6х+-х

KunLallalit KunLallalit    3   16.07.2019 10:40    0

Ответы
МаксимНелучший МаксимНелучший  03.10.2020 05:35
3(х-1)+х=2х
3х-3+х=2х
4х-2х=3
2х=3
х=3/2
х=1 1/2
х=1,5

5-х=4(х-3)
5-х=4х-12
4х+х=5+12
5х=17
х=17/5
х=3 2/5
х=3,4

5(х+4)+х=6
5х+20+х=6
6х=6-20
6х=-14
х=-14/2
х=-7

7-(2х+3)=9
7-2х-3=9
-2х=9-7+3
-2х=5
х=5:(-2)
х=-5/2
х=-2 1/2
х=-2,5

3(х-7)-6х=-х
3х-21-6х=-х
-3х+х=21
-2х=21
х=21:(-2)
х=-10 1/2
х=-10,5
ПОКАЗАТЬ ОТВЕТЫ
sosubivaet1 sosubivaet1  03.10.2020 05:35
3x-3+x=2x
3x+x-2x=3
2x=3
x=1.5

5-x=4x-12
-x-4x=-12-5
-5x=17
x=-3.4

7-2x+3=9
-2x=9-7-3
-2x=-1
x=0.5

3x-21-6x=-x
3x-6x+x=21
-2x=21
x=-20.5
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика